Pelatihan Laporan Keuangan Dasar Bagi Pelaku Rumah Umkm Labuhanbatu - Purba, Elvitrianim; Trianovie, Sri; Saehan, A (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2023)
Abstract is a brief summary of the article to help readers quickly determine the purpose of the research and according to research needs. Abstract should be clear and informative, providing a statement for the problem under study and its solution. Abstract length between 90 to 230 words. Avoid unusual abbreviations and define all symbols used in the abstract. The abstract contains problems from the initial objectives of the service implementation, solutions to problem solving offered, as well as the percentage of success of the activities carried out which are shown in a graph. Using keywords related to the research topic is recommended.